Effects of Hepatitis C Virus (HCV) Eradication on Bone Mineral Density in Human Immunodeficiency Virus/HCV-Coinfected Patients. (15th September 2020) - Carrero, Ana; Berenguer, Juan; Hontañón, Víctor; Guardiola, Josep M; Navarro, Jordi; von Wichmann, Miguel A; Téllez, María J; Quereda, Carmen; Santos, Ignacio; Sanz, José; Galindo, María J; Hernández-Quero, José; et al.
Abstract: Background: Little is known about the effects of eradication of hepatitis C virus (HCV) on bone mineral density (BMD) and biomarkers of bone remodeling in human immunodeficiency virus (HIV)/HCV-coinfected patients. Methods: We prospectively assessed standardized BMD (sBMD) at the lumbar spine and femoral neck, World Health Organization BMD categories at both sites, and plasma concentrations of soluble receptor activator of NF-κβ ligand (sRANKL), and osteoprotegerin (OPG) at baseline (the date of initiation of anti-HCV therapy) and at 96 weeks. Results: A total of 238 patients were included. The median age was 49.5 years, 76.5% were males, 48.3% had cirrhosis, 98.3% were on antiretroviral therapy, median CD4 + cell count was 527 cells/μL, and 86.6% had HIV-1 RNA <50 copies/mL. The prevalence of osteoporosis at baseline at the lumbar spine (LS) and femoral neck (FN) was 17.6% and 7.2%, respectively. Anti-HCV therapy comprised pegylated interferon (peg-IFN) and ribavirin (RBV) plus 1 direct-acting antiviral in 53.4%, peg-IFN/RBV in 34.5%, and sofosbuvir/RBV in 12.2%. A total of 145 (60.9%) patients achieved sustained virologic response (SVR). No significant effect of SVR was observed on sBMD for the interaction between time and SVR either in the LS ( P  = .801) or the FN ( P  = .911). Likewise, no significant effect of SVR was observed in plasma levels of sRANKL ( P  = .205), OPG ( P  = .249), or sRANKL/OPG ratio ( P  = .123) for the interaction between time and SVR. No significant correlation was found between fibrosis by transient elastography, and LS and FN sBMD, at baseline and week 96. Conclusions: SVR was not associated with significant changes in BMD nor biomarkers of bone remodeling in HIV/HCV-coinfected persons. Abstract : Eradication of hepatitis C virus (HCV) following anti-HCV therapy was not associated with significant changes in bone mineral density or biomarkers of bone remodeling in HIV/HCV-coinfected persons.